Securing Wireless Communications at the Physical Layer - Liu, Ruoheng.; Trappe, Wade. (Springer US, 2010)
Wireless systems are becoming increasingly pervasive and securing these systems has been challenging, in large part due to the unique properties associated with wireless communications. Securing these networks has traditionally been approached by taking a conventional approach involving cryptographic protocols. Such an approach inherently seeks to secure the wireless network at the link layer and above, and consequently fails to leverage the most unique characteristic of wireless communication: its physical layer. Securing Wireless Communications at the Physical Layer is a compilation of contributions by experts in wireless communications and security, and presents state-of-the-art results that examine the challenge of introducing security at the physical layer of a wireless system. Throughout this book there is an underlying theme that the rich multipath environment that is typical of wireless scenarios supports the establishment of new security services at the physical layer, including new mechanisms that establish cryptographic keys, that support communication with assured confidentiality, and that can authenticate transmitters in mobile environments. The book takes a holistic approach to covering topics related to physical layer security solutions, with contributions ranging from the theoretical underpinnings behind secure communications to practical systems validations that have been performed on real wireless systems. The book also covers topics related to ensuring that cooperative wireless communications at the physical layer is trustworthy. Additionally, the emerging area of modulation forensics, whereby a device is able to identify the modulation format being employed by other devices is explored. Securing Wireless Communications at the Physical Layer will serve as a valuable reference to engineers and researchers in the fields of security and wireless communications.